FUNGSI PARTAI DALAM PARLEMEN - Marudut Parulian Silitonga; Hotben M. Lumban Gaol (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This essay explores the crucial roles that political parties play in the legislature and emphasizes how important they are to representative democracy. As the major conduit between the people and the government, political parties play a crucial role in establishing state policies and upholding a stable, responsible political system. The main tasks that parties carry out in parliament are described in this analysis: legislation, which involves proposing, debating, and approving laws; representation, which involves directing public desires into policy; oversight, or political control, which guarantees checks and balances by keeping an eye on the executive branch; political recruitment, which involves choosing and preparing legislative candidates; and political stabilization, which involves handling conflict and preserving national stability.The study makes the case that the execution of these functions in Indonesia is fraught with difficulties, such as inadequate internal party democracy, poor cadre development, practical hiring procedures, elite dominance, and inadequate government oversight as a result of transactional coalition politics. The study comes to the conclusion that extensive internal party reform, improved political education, and increased accountability and transparency are necessary to strengthen these roles.